The Occurrences of Hedges and Boosters in ELT Learners' Academic Written Discourses - Puspa Linda Hapsari, - (2020)
As parts of interactional metadiscourse devices, hedges concern with the communicative strategies used for lessening the claims of certain utterances, contrastively, boosters are used to strengthen claims of certain utterances. Despite considerable studies on hedges and boosters had been undertaken, there has been limited studies focusing on the occurrences of both hedges and boosters in written discourse. Adapting the taxonomy of hedges proposed by Hyland (1998) and Varttala (2001) as well as the taxonomy of boosters proposed by Hinkel (2005), a descriptive study evolving a corpus-based approach was conducted in attempt to explore the use of hedges and boosters employed in ELT learners' thesis discussion section. Then, a further to analysis of the impact of hedges and boosters towards the quality of arguments in the thesis was also done by using Toulmin's (2003) scheme of argumentation. The result showed that, firstly, hedging devices were dominantly found within the category of modal verbs consisting the total of 305 tokens, while in terms of boosters, the most frequently appeared tokens occured within the category of emphatics, amounting the total of 126 tokens. Then, regarding the impact of hedges and boosters towards the quality of arguments in the ELT learners' thesis, boosters play important roles such as strengthening the claim in the thesis statement and validating the data, while the use of hedges are crucial to open more room interpretation for readers by the use of presenting conclusions and contradictory views toward certain preceeding claims. It is concluded that Indonesian ELT learners students prefer tentative expression rather than performing confidence.